2012
DOI: 10.1038/ng.1039
|View full text |Cite
|
Sign up to set email alerts
|

Amplification of siRNA in Caenorhabditis elegans generates a transgenerational sequence-targeted histone H3 lysine 9 methylation footprint

Abstract: Exogenous double-stranded RNA (dsRNA) has been shown to exert homology-dependent effects at the level of both target mRNA stability and chromatin structure. Using C. elegans undergoing RNAi as an animal model, we have investigated the generality, scope, and longevity of chromatin-targeted dsRNA effects and their dependence on components of the RNAi machinery. Using high-resolution genome-wide chromatin profiling, we found that a diverse set of genes can be induced to acquire locus-specific enrichment of H3K9 t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

11
281
1

Year Published

2012
2012
2022
2022

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 248 publications
(299 citation statements)
references
References 70 publications
11
281
1
Order By: Relevance
“…S1), the mechanisms that are required for transgenerational stability of silencing could be initiated in progeny-potentially during germline development. Thus, the production of secondary small RNAs and deposition of chromatin modifications proposed to be required for transgenerational gene silencing (15,24,29,(39)(40)(41) could be initiated in progeny when parents encounter dsRNA. These considerations also impact the interpretation of experiments evaluating the duration of transgenerational inheritance in response to RNAi (25,42).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…S1), the mechanisms that are required for transgenerational stability of silencing could be initiated in progeny-potentially during germline development. Thus, the production of secondary small RNAs and deposition of chromatin modifications proposed to be required for transgenerational gene silencing (15,24,29,(39)(40)(41) could be initiated in progeny when parents encounter dsRNA. These considerations also impact the interpretation of experiments evaluating the duration of transgenerational inheritance in response to RNAi (25,42).…”
Section: Discussionmentioning
confidence: 99%
“…22). Although secondary small RNAs and chromatin marks have been detected in progeny upon parental exposure to dsRNA (23,24), it is unknown where extracellular dsRNA needs to interact with intracellular RNA or DNA to cause gene silencing in progeny.…”
mentioning
confidence: 99%
“…In particular, our model does not address the mechanisms by which these marks are transmitted during or after replication, although we have previously shown that straightforward variations of the model can provide the means for epigenetic memory of the mark (20). Other potential mechanisms for epigenetic memory include factors that promote continued recruitment of marking factors to the target site, such as antisense RNA-based targeting of H3K9me3 silencing factors (34,35).…”
Section: Discussionmentioning
confidence: 99%
“…Indeed, in worms which are mutants for the RdRP RRF-1, inherited RNAi diminishes after 2 generations, indicating the RNA amplification is required for long-term transgenerational RNAi effects [21,24]. In addition, it was recently demonstrated that the RRF-1 RdRP is required for effective transgenerational targeting of chromatin [25]. The inherited effect of RNAi on chromatin was shown to be mediated by HRDE-1 (heritable RNAi defective-1, also named WAGO-9; for Worm Specific Argonaute 9) and Nuclear RNAi factors (NRDEs, for Nuclear RNAi Defective).…”
Section: And Text Box)mentioning
confidence: 99%